The direct effects of media exposure on behaviors aimed at preventing COVID-19 and its indirect effects as mediated by interpersonal communication: a longitudinal study in Japan - Okada, Hiroko; Okuhara, Tsuyoshi; Kiuchi, Takahiro (Frontiers in Public Health, 2024)
Objective We aimed to examine the direct effects of exposure to media information about infection-preventing behavior and its indirect effects via interpersonal communication at two time points during the pandemic. Methods In August 2020 and August 2021, a web-based survey of Japanese people under a declared state of emergency was conducted. We collected sociodemographic data and data on seven types of exposure to media information, three types of exposure to interpersonal communication, and six types of infection-preventing behavior. Results A total of 784 participants completed both surveys. Exposure to information in the mass media decreased over the year, while interpersonal communication about COVID-19-related topics increased. The direct effect of exposure to information in the media about preventive behaviors was statistically significant in the pandemic’s early stages, but this was no longer true after 1 year. The indirect effect via interpersonal communication was statistically significant at both time points. Conclusion Our results suggest that the influence of media information on infection-preventing behavior during the pandemic was maintained over time as an indirect effect via interpersonal communication. For risk communication media strategies during pandemics, adopting strategies to generate interpersonal communication will have a sustained effect on preventive behavior.